Budowa ciała uczniów technikum i traktorzystów - Gościcka, Danuta; Klaus, Ewa (Polskie Towarzystwo Antropologiczne, 1988)
BODY BUILD OF POLYTECHNIC PUPILS AND TRACTOR DRIVERS. The weight-and-height Rohrer’s index was calculated for 102 pupils of the Polytechnic for Agiculture Mechanization and 160 tractor drivers employed in state-owned farms.* It was found out that with age the pupils developed a tendency towards an athletic body build, whereas the tractor drivers with the passage of years of work a tendency towards a pyknic body build.
BODY BUILD OF POLYTECHNIC PUPILS AND TRACTOR DRIVERS